2022
DOI: 10.1111/jvh.13705
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment for hepatitis C virus direct‐acting antiviral therapy virological failure in primary and tertiary settings: The REACH‐C cohort

Abstract: Virological failure occurs in a small proportion of people treated for hepatitis C virus (HCV) with direct-acting antiviral (DAA) therapies. This study assessed retreatment for virological failure in a large real-world cohort. REACH-C is an Australian observational study (n = 10,843) evaluating treatment outcomes of sequential DAA initiations across 33 health services between March 2016 to June 2019. Virological failure retreatment data were collected until October 2020. Of 408 people with virological failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Our results revealed that the SVR 12 rates were 97.2% and 100% in the EP and PP populations, which were comparable to the Western studies and meta-analysis reporting the SVR 12 rates of 90-100%. [21][22][23][24][25][26][27][28][29]38 Our results corroborated the SOF/VEL/VOX's excellent effectiveness in managing patients previously treated with NS5A inhibitors, regardless of ethnicity. 30,31 Our study revealed that no speci c patient, viral, or treatment factors predicted treatment responses.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our results revealed that the SVR 12 rates were 97.2% and 100% in the EP and PP populations, which were comparable to the Western studies and meta-analysis reporting the SVR 12 rates of 90-100%. [21][22][23][24][25][26][27][28][29]38 Our results corroborated the SOF/VEL/VOX's excellent effectiveness in managing patients previously treated with NS5A inhibitors, regardless of ethnicity. 30,31 Our study revealed that no speci c patient, viral, or treatment factors predicted treatment responses.…”
Section: Discussionsupporting
confidence: 72%
“…36,39−41 Although some real-world studies indicated that patients with HCV GT3 infection, cirrhosis, previous SOF/VEL treatment, and multiple RASs might adversely affect the SVR 12 rate, the POLARIS-1 trial and the other real-world studies, including ours, did not show such association. [21][22][23][24][25][26][27][28][29]41 those with SOF/VEL/VOX alone. 24,26 While the EASL guidelines recommend SOF/VEL/VOX plus RBV for "di cult-to-cure" patients to intensify the retreatment responses, the AASLD guidelines do not endorse the universal combination except for cirrhotic patients with HCV GT3 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most are small in scale, with some reporting high losses to follow-up. Overlapping risk factors for treatment discontinuation and loss to follow-up are described 6 , 19 21 and could lead to underestimations of treatment discontinuation in clinical studies. With all HCV treatment in Australia delivered through the PBS and half of the estimated population with HCV treated between 2016 and 2021, 22 this analysis provides a highly representative picture of treatment discontinuation at a national level.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a broad range of intrapersonal, interpersonal, and structural factors that impact treatment discontinuation. 19 , 32 Patient-centered interventions that promote adherence to treatment and retention in HCV care for at-risk populations 33 , 34 will be critical if elimination is to be achieved. As the majority of prescribers in Australia, general practitioners play a critical role in HCV elimination efforts.…”
Section: Discussionmentioning
confidence: 99%